Pembuatan Batubata dengan Bahan Baku Lumpur Sidoarjo - Endang Srihari Mochni; Arief Budhyantoro (Bina Teknika, 2021)
Many attempts to reduce the volume of Sidoarjo mudflow that came out, one of which is the use of Sidoarjo mud for making bricks. The results of research in the chemical laboratory show that the Sidoarjo mud mineral content is mostly silica and alumina minerals, so it is very supportive for use as a material for making bricks. Making bricks requires mixed materials, one of which is paper sludge. Paper sludge waste is discharged from the paper industry, which can pollute the environment if it is discharged directly into the environment. Therefore, a solution is needed by utilizing the potential of the sludge waste. One of them is by using paper sludge as an additive in making bricks, because most of the components of paper sludge waste are calcium carbonate. In building materials, calcium carbonate can function as an additive so that paper sludge waste can be used as an additional material in making bricks. The purpose of this study is to determine the best ratio of Sidoarjo mud with paper sludge to the quality of the bricks, find out the best combustion temperature to the quality of the bricks produced, and compare the quality of the bricks before and after burning. The bricks are synthesized with a variation of the ratio of Sidoarjo mud raw material and paper sludge (1: 0, 1: 1, 2: 1, 3: 1) and variations in combustion temperature (no combustion, 400°C, 450°C, 500°C, 750°C, 900°C). In this study, the best quality of bricks according to SNI is 2: 1 ratio bricks with a combustion temperature of 750 ° C. The ratio of 2: 1 brick with a combustion temperature of 750°C has a percentage of water absorption of 17.17% and compressive strength of 37.78 kg / cm2.